River Lamprey Lampetra fluviatilis (L.) Fishing in the Area around the Baltic Sea - Sjöberg, Kjell (Journal of Northern Studies, 2012)
The river lamprey (Lampetra fluviatilis) was previously caught in large numbers in Europe when migrating up in the rivers during autumn for spawning the next spring. It was used as food and was also used as bait in cod fishing in the North Sea. Today the river lamprey has decreased in numbers over much of it’s distribution range, but in the Baltic Sea area, the population is still at a fairly good level, and fishing for lampreys as food (a tradition going back to at least the fifteenth century) is still going on in northern Swedish and Finnish rivers, as well as in coastal rivers in the southern Baltic Sea area. In this article the current situation as regards river lamprey fishing in Sweden, Finland, Latvia and, to some extent, Estonia, Lithuania and Poland is presented.